Makna Eksistensial Mainan sebagai Simbol Kebertahanan Emosi Anak dalam Film Toy Story 3 - Melysa, Melysa Putri Ayuningtyas; Ayuningtyas, Melysa Putri; Indah Puspitasari; Raras Hafiidha Sari (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study aims to uncover the existential meaning of toys as a symbol of children's emotional resilience in the film Toy Story 3. This Pixar film depicts the emotional journey between children and toys, which serve not only as entertainment but also as symbols of inner relationships, childhood memories, and the process of maturation. This study used a qualitative descriptive method with a symbolic and narrative analysis approach. Data were obtained through observation of scenes and dialogues of the main characters, namely Andy, Woody, and Buzz. The results show that the toys in this film represent the emotional existence of children who struggle to maintain affection, loyalty, and togetherness amidst life's changes. The scene where Andy parted with his toys culminates in an existential reflection on the meaning of loss and emotional maturity. Toy Story 3 teaches humanitarian values ​​about how humans, like toys, gain meaning in life through love, sacrifice, and togetherness. Keywords: Children’s Literature, Existential Meaning, Children's Emotions